2012
DOI: 10.1111/evo.12028
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Versus Phylogenetic Determinants of Trophic Associations in a Plant-Leafminer-Parasitoid Food Web

Abstract: Specialized trophic interactions in plant-herbivore-parasitoid food webs can spur "bottom-up" diversification if speciation in plants leads to host-shift driven divergence in insect herbivores, and if the effect then cascades up to the third trophic level.Conversely, parasitoids that search for victims on certain plant taxa may trigger "top-down" diversification by pushing herbivores into "enemy-free space" on novel hosts. We used phylogenetic regression methods to compare the relative importance of ecology ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 61 publications
3
39
0
Order By: Relevance
“…From a predator’s perspective, coevolution and escalation differ in what selective agents are responsible: the defense of a prey, or the attack by a predator. From a tenthredinid’s perspective, the present study and others indicate that sawfly species face guilds of vertebrate and invertebrate predators, but also parasitoids and pathogens [109-113]. Chemicals conform but also differ in their bioactivity on distant taxonomic groups such as invertebrates and vertebrates.…”
Section: Discussionmentioning
confidence: 57%
“…From a predator’s perspective, coevolution and escalation differ in what selective agents are responsible: the defense of a prey, or the attack by a predator. From a tenthredinid’s perspective, the present study and others indicate that sawfly species face guilds of vertebrate and invertebrate predators, but also parasitoids and pathogens [109-113]. Chemicals conform but also differ in their bioactivity on distant taxonomic groups such as invertebrates and vertebrates.…”
Section: Discussionmentioning
confidence: 57%
“…For example, the parasitoid community of leaf miners is characterized by the dominance of eulophid larval parasitoids (Hespenheide 1991, Kato 1996, Lewis et al 2002, that of lepidopteran gallers is characterized predominantly by parasitoids belonging to Eurytomidae, Torymidae, and Eupelmidae (Askew and Shaw 1986), and that of lepidopteran external feeders is characterized mainly by dipteran parasitoids in the family Tachinidae (Stireman and Singer 2003). In addition, previous studies have reported the influence of the host plant on parasitoid community structure: insect species using related host plants tended to share parasitoids or show similar parasitoid community structure (Askew and Shaw 1974, Hoffmeister 1992, Rott and Godfray 2000, Lill et al 2002, Bailey et al 2009, Leppa¨nen et al 2013). In addition, previous studies have reported the influence of the host plant on parasitoid community structure: insect species using related host plants tended to share parasitoids or show similar parasitoid community structure (Askew and Shaw 1974, Hoffmeister 1992, Rott and Godfray 2000, Lill et al 2002, Bailey et al 2009, Leppa¨nen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For Manuscript received 10 February 2014; revised 12 August 2014; accepted 4 September 2014; final version received 1 October 2014. For example, a comparison of the parasitoid community of leaf miners within the same genus showed that the host-plant effect was greater than the phylogenetic effect (Leppa¨nen et al 2013), whereas comparison among different orders indicated that the phylogenetic effect was greater than the host-plant effect (Lewis et al 2002). A. Rosenheim.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schulmeister 2003a; Ronquist et al 2012) are substantially under-represented with regards to tenthredinoids, especially the largest family, the Tenthredinidae. Nyman et al (1998Nyman et al ( , 2000Nyman et al ( , 2006Nyman et al ( , 2010 performed pioneering molecular analyses on the subfamily Nematinae to unravel their phylogeny and co-evolution with their host plants; Leppänen et al (2012Leppänen et al ( , 2013 similarly explored the leaf-mining Heterarthrinae. Isaka and Sato (2014) did a molecular phylogeny of mostly Palaearctic Selandriinae and estimated the time of origin and initial diversification for the subfamily to the Early Cretaceous.…”
Section: Introductionmentioning
confidence: 99%